Impacto da fadiga mental sobre o desempenho tático de jogadores de futebol em diferentes categorias - Guilherme de Oliveira Santos Silva (2024)
This study aims to compare the effects of mental fatigue on the tactical performance of soccer players in the under-13, under-15, and under-17 categories. The sample for this study consisted of 70 young elite athletes. Among them, 23 players from the under-13 category (12.6 ± 0.58 years old; 7.6 ± 1.03 years of experience in soccer), 23 players from the under-15 category (14.6 ± 0.47 years old; 8.6 ± 1.25 years of experience in soccer), and 24 players from the under-17 category (15.6 ± 0.66 years old; 9.5 ± 1.26 years of experience in soccer). The athletes participated in small-sided games in a 3 vs. 3 format with goalkeepers under experimental conditions, with the presence of mental fatigue, and control conditions, without the presence of mental fatigue. The induction of mental fatigue was carried out through an electronic version of the Stroop test for 20 minutes. Tactical performance was analyzed through the System of tactical assessment in Soccer (FUT-SAT), and measures of interpersonal synchronization in the In-phase pattern were recorded using 10 Hz GPS units. The significance level adopted in this study was 5% during the data analysis. For the synchronization variables, the MANOVA showed an interaction effect between Category*Condition (p = 0.003). It was observed that the under-15 category showed a significantly greater reduction than the under-17 category in the percentage of time in the in-phase synchronization pattern, in the depth axis, both in the offensive phase (p < 0.001) and defensive phase (p < 0.001), during the experimental condition. Furthermore, the under-15 category exhibited a significantly greater reduction than the under-13 category in the depth axis, both in the offensive phase (p < 0.001) and defensive phase (p < 0.001). Finally, the MANOVA did not show an interaction effect between Category*Condition (p = 0.155) in the effectiveness of executing tactical principles. However, subsequent ANOVAs and post-hoc Bonferroni tests allowed for the comparison of tactical performance, taking into account the control and experimental conditions. Consequently, it was possible to observe a reduction in overall defensive tactical performance (p = 0.02) and overall tactical performance (p = 0.002) in the experimental protocol. It is concluded that increased experience in the sport mitigates the detrimental effects of FM on tactical performance only in athletes whose maturation of inhibitory control systems is more advanced. Additionally, FM impaired overall offensive and defensive tactical performance regardless of the category.